2014
DOI: 10.7150/ijms.8916
|View full text |Cite
|
Sign up to set email alerts
|

New Oral Anticoagulants vs Vitamin K Antagonists: Benefits for Health-Related Quality of Life in Patients with Atrial Fibrillation

Abstract: New oral anticoagulants (NOAC) have demonstrated their efficacy as an alternative to vitamin K antagonists (VKA) in the prophylaxis of cardioembolic events in patients with atrial fibrillation (AF). However, evidence on the benefits of NOAC in health-related quality of life (HRQoL) is lacking.We evaluated changes in HRQoL related to oral anticoagulation therapy employing a specific questionnaire in a cohort of 416 patients with AF undergoing electrical cardioversion. In terms of HRQoL, we observed a progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 17 publications
(13 reference statements)
2
33
2
1
Order By: Relevance
“…There have been researches where the re-sults have been almost the same as in this study. Both researches state that at baseline NOAC users score better results than warfarin users [14]. But in this research we have found statistically signifi cant difference in separate section.…”
Section: Discussioncontrasting
confidence: 57%
“…There have been researches where the re-sults have been almost the same as in this study. Both researches state that at baseline NOAC users score better results than warfarin users [14]. But in this research we have found statistically signifi cant difference in separate section.…”
Section: Discussioncontrasting
confidence: 57%
“…Most of the existing studies either compare the HRQoL of these patients versus those on DOAC, or in a longitudinal manner. Ng et al, (34) Benzimra et al, (35) Contreras et al, (36) and Alegret et al, (37) have reported no signi cant difference in the HRQoL of patients with NVAF receiving long-term warfarin versus DOAC in real-world scenario. On the other hand, Balci et al reported signi cant improvement in every domain of SF-12v2 (all p < 0.001), (38) while de Caterina et al reported signi cant improvement in severe mobility problem (p = 0.003), pain/discomfort (p = 0.035), and anxiety/depression (p < 0.001) of EuroQoL Instrument 5 levels (EQ-5D-5L) among NVAF patients after switching from warfarin to DOAC.…”
Section: Discussionmentioning
confidence: 98%
“…Most of the existing studies either compare the HRQoL of these patients versus those on DOAC, or in a longitudinal manner. Ng et al, (30) Benzimra et al, (31) Contreras et al, (32) and Alegret et al, (33) have reported no signi cant difference in the HRQoL of patients with NVAF receiving long-term warfarin versus DOAC in real-world scenario. On the other hand, Balci et al reported signi cant improvement in every domain of SF-12v2 (all p < 0.001),(34) while de Caterina et al reported signi cant improvement in severe mobility problem (p = 0.003), pain/discomfort (p = 0.035), and anxiety/depression (p < 0.001) of EuroQoL Instrument 5 levels (EQ-5D-5L) among NVAF patients after switching from warfarin to DOAC.…”
Section: Treatment Satisfactionmentioning
confidence: 98%